At the centre of neuronal, synaptic and axonal pathology in murine prion disease: degeneration of neuroanatomically linked thalamic and brainstem nuclei. (30th May 2015) - Reis, Renata; Hennessy, Edel; Murray, Caoimhe; Griffin, Éadaoin W.; Cunningham, Colm
<x xml:space="preserve">Abstract</x> Aims The processes by which neurons degenerate in chronic neurodegenerative diseases remain unclear. Synaptic loss and axonal pathology frequently precede neuronal loss and protein aggregation demonstrably spreads along neuroanatomical pathways in many neurodegenerative diseases. The spread of neuronal pathology is less studied. Methods We previously demonstrated severe neurodegeneration in the posterior thalamus of multiple prion disease strains. Here we used the ME7 model of prion disease to examine the nature of this degeneration in the posterior thalamus and the major brainstem projections into this region. Results We objectively quantified neurological decline between 16 and 18 weeks post‐inoculation and observed thalamic subregion‐selective neuronal, synaptic and axonal pathology while demonstrating relatively uniform protease‐resistant prion protein (PrP) aggregation and microgliosis across the posterior thalamus. Novel amyloid precursor protein (APP) pathology was particularly prominent in the thalamic posterior (PO) and ventroposterior lateral (VPL) nuclei. The brainstem nuclei forming the major projections to these thalamic nuclei were examined. Massive neuronal loss in the PO was not matched by significant neuronal loss in the interpolaris (Sp5I), while massive synaptic loss in the ventral posteromedial nucleus (VPM) did correspond with significant neuronal loss in the principal trigeminal nucleus. Likewise, significant VPL synaptic loss was matched by significant neuronal loss in the gracile and cuneate nuclei. Conclusion These findings demonstrate significant spread of neuronal pathology from the thalamus to the brainstem in prion disease. The divergent neuropathological features in adjacent neuronal populations demonstrates that there are discrete pathways to neurodegeneration in different neuronal populations.